2020
DOI: 10.7717/peerj.8924
|View full text |Cite
|
Sign up to set email alerts
|

Impact of proximal cavities and primary molar absence on space in the dental arches

Abstract: Background A recently proposed treatment protocol for dental caries in primary teeth, called Ultra Conservative Treatment (UCT), keeps medium to large cavities open so that children can keep them clean with tooth brushing and fluoride toothpaste. However, carious lesions have been related to malocclusion and decrease of space for the eruption of the permanent successor. Methods This cross-sectional study evaluated dental casts of 235 schoolchildren, aged 6–7 years old of six public schools in deprived suburb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Measurements were carried out digitally on standardized occlusal pictures of the plaster casts. The method to obtain the occlusal pictures have been described elsewhere ( Gomide et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements were carried out digitally on standardized occlusal pictures of the plaster casts. The method to obtain the occlusal pictures have been described elsewhere ( Gomide et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that extensive cavities in proximal surfaces of primary teeth are associated with a decrease of space in the primary molar region, known as the D+E space ( Northway & Wainright, 1980 ; Gomide et al, 2020b ). Decrease of the D+E space may have orthodontic implications ( Stahl & Grabowski, 2004 ), since it tends to reduce the available space for the eruption of the permanent canine and the premolars, which may affect alignment of the successor teeth and/or cause tooth impaction ( Northway, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term use of a lingual arch increases the risk of dental caries, however 8) . In addition, caries developing at the contact points of deciduous molars results in a greater amount of lost space, leading to malformation of the dentition 7) . It has also been shown that crowding naturally decreases between the period of early mixed dentition and that of the early permanent dentition due to the influence of leeway space and other factors 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, leeway space has been shown to be clinically significant in terms of a range of factors, including normal tooth contact, anterior tooth replacement and tooth axis stability, lateral tooth group facing and cusp fitting, and the first molar occlusal relationship 15) . Because of its importance, leeway space continues to draw attention in the literature 1,3,5,7) .…”
Section: Introductionmentioning
confidence: 99%
“…By the time they reach 6 years of age, and their primary dentition is complete, the reported worldwide prevalence of dental caries is 48% (1), making it the 10th most common condition in the world (2). This preventable, biofilm-mediated, lifestyle-driven disease harms children's health and wellbeing (3), impacting negatively on their quality of life, resulting in pain, early tooth loss along with impaired function, growth, esthetics (4,5) and loss of time at school (6).…”
Section: Introductionmentioning
confidence: 99%